Starch-based biofilms for green packaging - Ali, R. R. (Springer US, 2013)
The aim of this study is to develop degradable starch-based packaging film with enhanced mechanical properties. A series of low-density polyethylene (LDPE)/tapioca starch compounds with various tapioca starch contents were prepared by twin-screw extrusion with the addition of maleic anhydride-grafted polyethylene as compatibilizer. Palm cooking oil was used as processing aid to ease the blown film process; thus, degradable film can be processed via conventional blown film machine. Studies on their mechanical properties and biodegradation were carried out by tensile test and exposure to fungi environment, respectively. The presence of high starch contents had an adverse effect on the tensile properties of LDPE/tapioca starch blends. However, the addition of compatibilizer to the blends improved the interfacial adhesion between the two materials and hence improved the tensile properties of the films. High content of starch was also found to increase the rate of biodegradability of LDPE/tapioca starch films. It can be proved by exposure of the film to fungi environment. A growth of microbes colony can be seen on the surface of LDPE/tapioca starch film indicates that the granular starch present on the surface of the polymer film is attacked by microorganisms, until most of it is assimilated as a carbon source.